156 THE IMPACT OF PNEUMOCOCCAL VACCINES IN ADULTS WITH SINOPULMONARY INFECTIONS AND LOW PNEUMOCOCCAL ANTIBODY TITERS: PILOT OBSERVATIONS. (1st January 2005) - Yao, L.; Kumar, P.
Abstract : Rationale: The studies on the impact of pneumococcal vaccines in recurrent respiratory infections in patients with low pneumococcal antibody titers were performed only in children. This pilot project is focused on adult patients. Methods: Four patients with recurrent sinopulmonary infections and low pneumococcal antibody titers but normal immunoglobulins were studied. All of the patients received pneumococcal polysaccharide vaccines. Repeat titers were obtained 4 weeks after the vaccines. Three patients demonstrated three-fold increases or above 1.5 μg/mL in more than 70% of the serotypes of pneumococcal titers, which was considered a good response. The fourth patient, who failed to respond to pneumococcal polysaccharide vaccine, did respond to pneumococcal conjugate vaccine. The patients were followed every 3 months up to a year. Results: Significant clinical improvements had already been noted in 2 out of the 4 patients. One patient with a history of sinusitis with 6 to 7 sinus infections per year in the previous 5 years had only one episode 6 months after the vaccine was given. Another patient had 2 episodes of pneumonia and numerous sinus infections 4 years prior to the vaccine. This patient has had no evidence of pneumonia or sinusitis 1 year after the vaccination. The follow-up period in the remaining patients has been too short to draw meaningful conclusions. Conclusions: The observations suggest that adults with low pneumococcal antibody titers and recurrent respiratory infections may show serological and clinical improvements after use of pneumococcal vaccines.